Isolated Rupture of the Teres Major Muscle When Water Skiing: A Case Report and Literature Review. (1st April 2018) - Cousin, Julien; Crenn, Vincent; Fouasson-Chailloux, Alban; Dauty, Marc; Fradin, Philippe; Gouin, Francois; Venet, Guillaume
Abstract : Isolated lesions to the teres major muscle are rare. They generally occur in patients participating in sports such as baseball, tennis, or boxing. We report the case of a sports patient who suffered an isolated injury to the teres major while water skiing. The clinical presentation was confirmed by MRI. Conservative treatment was chosen and consisted of brief analgesic immobilization, followed by rehabilitative treatment. The rapid recovery of this patient with normal isokinetic strength evaluation at 6 months was interesting for objectifying full muscle recovery. Our results and the data from the literature suggest that functional rather than surgical treatment is preferable in isolated lesions to the teres major muscle.